Multiwavelength observations of MAXI J1820+070 during its outburst decay and subsequent mini-outburst. Issue 3 (9th June 2022) - Özbey Arabacı, M; Kalemci, E; Dinçer, T; Bailyn, C D; Altamirano, D; Ak, T
ABSTRACT: We present results from quasi-simultaneous multiwavelength observations of the Galactic black hole X-ray transient MAXI J1820+070 during the decay of the 2018 outburst and its entire subsequent mini-outburst in March 2019. We fit the X-ray spectra with phenomenological and Comptonizaton models and discuss the X-ray spectral evolution in comparison with the multiwavelength behaviour of the system. The system showed a rebrightening in UV/Optical/NIR bands 7 d after the soft-to-hard transition during the main outburst decay while it was fading in X-rays and radio. In contrast, the mini-outburst occurred 165 d after the hard state transition of the initial outburst decay and was detected in all wavelengths. For both events, the measured time-scales are consistent with those observed in other black hole systems. Contemporaneous hard X-ray/soft γ-ray observations indicate a non-thermal electron energy distribution at the beginning of the UV/Optical/NIR rebrightening, whereas a thermal distribution can fit the data during the hard mini-outburst activity. The broad-band spectral energy distributions until the rebrightening are consistent with the irradiated outer accretion disc model. However, both the SEDs produced for the peak of rebrightening and close to the peak of mini-outburst provided good fits only with an additional power law component in the UV/Optical/NIR frequency ranges, which is often interpreted with a jet origin.